Comparative Efficacy and Effectiveness in the Drug Treatment of Schizophrenia - Geddes, J; Stroup, T; Lieberman, J (Wiley-Blackwell, 2011)
Effective drug treatment for schizophrenia became available in the 1950s and lead to a revolution in care, allowing many patients to return to the community and remain well for extended periods. The first-generation antipsychotics (FGAs) caused frequently disabling adverse effects, particularly extrapyramidal symptoms (EPS). Second-generation antipsychotics (SGAs), based on the exemplar of clozapine, are less likely to cause EPS. Both SGAs and FGAs are heterogeneous groups of drugs and may not represent distinct classes. Although clozapine has shown consistent and meaningful efficacy advantages over other antipsychotics, only some of the other SGAs appear to be more effective than FGAs and these advantages are small. Although SGAs tend to share a lower propensity to cause EPS than FGAs, their risk of other adverse events is substantial. Trials comparing the effectiveness of antipsychotics have diverse goals that should be considered when interpreting study findings. © 2011 Blackwell Publishing Ltd.